The hunting farmers : understanding ancient human subsistence in the central part of the Korean peninsula during the Late Holocene - Kwak, Seungki, (Archaeopress Publishing Ltd, 2017)
The central hypothesis of this research is that there was a wide range of resource utilization along with rice farming around 3,400-2,600 BP. This hypothesis contrasts with prevailing rice-based models, where climatically driven intensive rice agriculture from 3,400 BP is thought to be the dominant subsistence strategy that drove social complexity.